2018
DOI: 10.1161/strokeaha.117.019896
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus Neutrophil Extracellular Traps Content Impair tPA-Induced Thrombolysis in Acute Ischemic Stroke

Abstract: URL: http://www.clinicaltrials.gov. Unique identifier: NCT02907736.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
269
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(298 citation statements)
references
References 12 publications
12
269
0
3
Order By: Relevance
“…Our previous in vitro [15] and a recent ex vivo [16] study provided evidence that NET components (DNA, histones) modify the structure of fibrin, increase its mechanical stability and render clots less sensitive to lysis with tissue-type plasminogen activator/plasminogen. In line with the recently reported findings in ischemic stroke thrombi [16,17], our present work confirms the presence of NET components in AIS thrombi, but we also demonstrate that extracellular DNA content -the major meshwork-forming constituent of NETs -of AIS (median FD50 of 0.208) thrombi is similar to CAD and 2.5-fold lower than in PAD thrombi (median FD50 of 0.082, p=0.0013, Figure 1). Thus, compared to other artery locations, in AIS the NET meshwork impedes the least the fibrinolytic therapeutic approach to restore the patency of occluded vessels, a fact that deserves attention when making therapeutic decisions in stroke.…”
Section: Extracellular Dna and Ch3supporting
confidence: 93%
See 2 more Smart Citations
“…Our previous in vitro [15] and a recent ex vivo [16] study provided evidence that NET components (DNA, histones) modify the structure of fibrin, increase its mechanical stability and render clots less sensitive to lysis with tissue-type plasminogen activator/plasminogen. In line with the recently reported findings in ischemic stroke thrombi [16,17], our present work confirms the presence of NET components in AIS thrombi, but we also demonstrate that extracellular DNA content -the major meshwork-forming constituent of NETs -of AIS (median FD50 of 0.208) thrombi is similar to CAD and 2.5-fold lower than in PAD thrombi (median FD50 of 0.082, p=0.0013, Figure 1). Thus, compared to other artery locations, in AIS the NET meshwork impedes the least the fibrinolytic therapeutic approach to restore the patency of occluded vessels, a fact that deserves attention when making therapeutic decisions in stroke.…”
Section: Extracellular Dna and Ch3supporting
confidence: 93%
“…Strong evidence supports the role of NETs in both deep venous [7][8][9][10][11] and arterial thrombi [12][13][14], and they are now regarded as an additional scaffold of thrombus formation tightly intertwined with the fibrin matrix. In a previous study, we demonstrated massive presence of extracellular DNA and histones in thrombi removed with surgery from patients with PAD [15] and recent studies showed the presence of NETs in ischemic stroke thrombi [16,17].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Scale, 10 µm tissue-type plasminogen activator-induced thrombolysis of these thrombi ex vivo (61,62), which again indicates that thrombo-inflammatory clots require breakage of their nucleic acid component to achieve resolution.…”
mentioning
confidence: 99%
“…Some of the most recent work has made it clear that combining PA encapsulation with magnetic localization, ultrasound, and hyperthermia may produce lysis rates up to an order of magnitude faster than those achievable using free PA. Engineered particles also allow for the delivery of two or more agents, which could be exploited to couple PA with other emerging thrombolytics targeted to von Willebrand factor, neutrophil extracellular traps, and thrombin‐activatable fibrinolysis inhibitor and PAI‐1; alternatively, PA could be delivered alongside adjuvants that enhance PA activity, PAI‐1 inhibitors, or FXIIIa inhibitors to accelerate thrombolysis …”
Section: Discussionmentioning
confidence: 99%